Mythological and fantasy creatures in Marco Polo account for animation creation - Gong, Deyang (Nanyang Technological University, 2025)
Marco Polo (1254-1324) chronicled his travels to the East, claiming to have encountered fantasy creatures. However, those creatures may not be the mythological creatures considered today, Polo may meet the real-world animals that are familiar today but were novel to Westerners back in the 13 century and mistook them as fantasy beings. While current research may more focus on the proof of the real-world animals that Polo may meet based on the animals’ living habitats and habits, as well as the geographical and historical facts of the locations, this project focuses on the creatures’ appearance and visual elements which could be assembled for animation creation. Following a structured approach, this research thoroughly reviews scholarly opinions and literature related to creatures in Marco Polo's account. Iconographic elements are identified by comparing the original descriptions of the fantasy creatures in Polo's account, findings of real-world animals, and fantasy creatures from other sources. The findings indicate that the "unicorn" Polo encountered is likely a rhino, while the "serpents" he encountered are more probably crocodiles. The analysis provides valuable insights for animators seeking creative representations of these creatures. This project contributes to the field of animation by providing a bridge between mythological creatures and their real-world counterparts, enabling the creation of captivating and authentic animated representations, which benefits both the researcher and other artists interested in the subject. Future work includes sourcing additional relevant materials for in-depth discussion, exploring other creatures mentioned in Polo's account, and utilizing the findings to design and produce animations.